Applicability of aluminum amalgam to the reduction of arylnitro groups. Issue 47 (19th November 2020) - Monsen, Paige J.; Luzzio, Frederick A.
Graphical abstract: Highlights: Short reaction times, rapid workup. Compatible with many functional groups. High yields. Abstract: An array of arylnitro compounds with various functionality were treated with freshly-prepared aluminum amalgam in THF/water solution and resulted in the corresponding arylamines. The Al(Hg)-mediated reductions are relatively rapid with consumption of the amalgam and disappearance of starting material occurring over 20–30 min. The workup of the reductions involves only removal of the insoluble by-products by filtration followed by concentration. Only in some cases is chromatography required to secure the pure product. The desired arylamines are furnished in quantities of 25–100 mg, which in some cases, could be taken on to the next reaction without further purification. Reductions of 4-nitrobenzyl derivatives of carbohydrates or nucleosides were selective in affording the corresponding 4-aminobenzyl products. To show applicability in click chemistry, selected aminobenzyl products are directly azidated to yield products that were then used in click reactions to afford the corresponding 1, 2, 3-triazoles.